Improving Lecturer Performance Through Strengthening Service Leadership, Empowerment, Achievement Motivation, And Trust in Muhammadiyah Tangerang University Lecturers - Mahpud; Sri Setyaningsih; Oding Sunardi (International Journal of Business and Social Science Research, 2024)
This research aims to produce strategies and ways to improve the performance of lecturers at the Muhammadiyah University of Tangerang by strengthening the variables of servant leadership, empowerment, achievement motivation, and trust as intervening variables. The research sample was 215 samples taken using stratified proportional random sampling of faculty lecturers. This research uses a survey method with a path analysis approach and SITOREM analysis. The results of this research can be concluded: 1). there is a direct influence between servant leadership on lecturer performance, 2) there is a direct influence between empowerment on lecturer performance, 3) there is a direct influence between achievement motivation on lecturer performance, 4) there is a direct influence between trust (X4) on lecturer performance (Y), 5) there is a direct influence between servant leadership on achievement motivation, 6) there is a direct influence between empowerment on achievement motivation, 7) there is a direct influence between servant leadership on trust, 8) there is a direct influence between empowerment on trust, 9) there is an indirect influence between servant leadership on lecturer performance through achievement motivation, 10) there is an indirect influence between empowerment on lecturer performance through achievement motivation, 11) there is an indirect influence between servant leadership on lecturer performance through trust, 12) there is an indirect influence between empowerment (X2) on lecturer performance through trust. The results of the SITOREM analysis show that based on the priority order of improving lecturer performance, it is necessary to strengthen servant leadership and empowerment. If servant leadership is to be strengthened, it is carried out by enhancing indicators that are still weak, namely: Listening, Vision, Healing, and Humility as well as maintaining or developing indicators: Wisdom, Service, Empathy, and Organizational Stewardship, empowerment wants to be strengthened, so this is done by improving indicators that are still weak, namely: Delegation of authority in work freedom, and Competency Building as well as maintaining or developing indicators: Modeling (exemplary) from individual superiors, Self-efficacy, and Organizational Support, achievement motivation want to be strengthened, so this is done by improving indicators that are still weak, namely: Encouragement to excel in competition, and Having a work plan that is systematic and can be realized, as well as maintaining or developing indicators: The need to work intensively (persistent, focused) in carrying out tasks, likes challenges and competition, the need for a successful career in the long term, and a strong urge to get feedback on performance and trust wants to be strengthened, so this is done by improving indicators that are still weak, namely: Consistent development , Giving authority with responsibility, and Shared responsibility, as well as maintaining or developing indicators: Mutual respect and support, and Communication and togetherness.